2015
DOI: 10.1002/path.4629
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5‐expressing stem cells are not the cells of origin of pyloric neuroendocrine carcinomas in mice

Abstract: In intestinal and pyloric epithelia, leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5)-expressing cells represent long-lived adult stem cells that give rise to all epithelial cell types, including endocrine cells. Ablation of the Apc gene in Lgr5-expressing cells leads to intestinal and pyloric adenomas. To assess whether all epithelial tumours of the gastrointestinal tract are derived from LGR5-positive stem cells, we crossed Lgr5-EGFP-IRES-creER(T2) mice, which express EGFP and Cre recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…After having collected evidence that both drug and target are present in the tumor, the preclinical efficacy of fasudil was monitored in living animals by PET/CT and post mortem by histopathological examination. Consistent with the known high metabolic and proliferative activity of the gastric tumor [27] , [28] , [45] , [ 18 F]-FDG uptake was clearly visible in an anatomical area corresponding to the localization of the pylorus, below the heart and above the two kidney signals. The 3D tumor volume (SUV (ccm)) was significantly reduced in therapy vs. control mice.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…After having collected evidence that both drug and target are present in the tumor, the preclinical efficacy of fasudil was monitored in living animals by PET/CT and post mortem by histopathological examination. Consistent with the known high metabolic and proliferative activity of the gastric tumor [27] , [28] , [45] , [ 18 F]-FDG uptake was clearly visible in an anatomical area corresponding to the localization of the pylorus, below the heart and above the two kidney signals. The 3D tumor volume (SUV (ccm)) was significantly reduced in therapy vs. control mice.…”
Section: Discussionsupporting
confidence: 69%
“…We resorted to a transgenic mouse model of GC [27] , where the viral oncogene SV40 large T-antigen is expressed as a transgene under the human CEA promoter specifically in the lower stomach (pylorus) of the mice, and which has been successfully subjected to pharmacological intervention by us before [32] , [43] , [44] . This tumor is characterized by early onset (within 4 weeks of age), a high proliferation index and up-regulation of stem cell (Wnt/Notch) [45] and neuroendocrine differentiation signatures [28] culminating in a small cell carcinoma of the lower part of the mouse stomach, the pylorus. At late stages, microinvasion and prolaps of luminal tumor nests toward the upper duodenum can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…By means of inducible lineage tracing of LGR5-positive adult stem cells in the CEA424-SV40-Tag model, the origin of the neuroendocrine carcinomas was more directly addressed. Results clearly separated SV40-Tag and LGR5 expression, respectively, consistent with long-lived pre-enteroendocrine precursor cells or reserve stem cells as putative tumor originating cells [185].…”
Section: Models Of Gep-net and Gep-necmentioning
confidence: 82%
“…As stated before, some stem cells contribute to the production of enteroendocrine cells in the gastric epithelium (Table 1), but whether these stem cells can directly give rise to neuroendocrine tumors is not well determined. For example, results from animal models indicated that Lgr5 + cells may not be the origin cells for pyloric neuroendocrine carcinomas, though this subtype stem cells give rise to endocrine cells in this region (Vetter et al, 2016). Besides, evidence for the interaction between enteroendocrine cells and stem cells is limited.…”
Section: Gastric Carcinogenesismentioning
confidence: 99%